Systemic Autoimmune, Rheumatic Diseases and Coinciding Psoriasis: Data from a Large Single-Centre Registry and Review of the Literature - Anna Bazsó; Péter Szodoray; Ágnes Szappanos; Judit Korda; Patrícia Pálfi; Emese Kiss; Gyula Poór (Hindawi Limited, 2015)
Psoriasis is a systemic immune-inflammatory disease characterized by chronic or recurrent skin symptoms, psoriatic arthritis, enthesopathy, and uveitis. Psoriasis has recently been published to appear with various autoimmune disorders, but the coexistence has been systematically reviewed by only few studies until now. In the present study, charts and electronic database of 4344 patients with various systemic autoimmune disorders, under regular medical control at our department, were reviewed retrospectively searching for association with psoriasis. Hereby, we demonstrate 25 psoriatic patients coinciding with various systemic autoimmune diseases. The coexistence of psoriasis and autoimmune diseases resulted in the worsening of the clinical outcome of the autoimmune diseases as indicated by higher frequency and dosages of glucocorticoid use, need for biologicals, and other comorbidities. These results suggest common environmental and genetic background as well as therapeutic possibilities in the future.